Leaky Integrate‐and‐Fire Mechanism in Exciton–Polariton Condensates for Photonic Spiking Neurons (Laser Photonics Rev. 17(1)/2023). Issue 1 (13th January 2023) - Tyszka, Krzysztof; Furman, Magdalena; Mirek, Rafał; Król, Mateusz; Opala, Andrzej; Seredyński, Bartłomiej; Suffczyński, Jan; Pacuski, Wojciech; Matuszewski, Michał; Szczytko, Jacek; Piętka, Barbara
Abstract : Neuromorphic Photonics In article number 2100660, Krzysztof Tyszka, Barbara Piętka, and colleagues introduce a new approach to neuromorphic photonics which employs the dynamics of strong exciton‐photon interaction to imitate the most fundamental functionalities of biological neurons, i.e. the "leaky integrate‐and‐fire" mechanism. Such systems can work as building blocks of future optical spiking neurons providing at least three orders higher processing speed and one order higher energy efficiency in comparison to electronic solutions.